A Methodological Framework to Assess the Thermal Performance of Green Infrastructure Through Airborne Remote Sensing. (2017) - Koc, Carlos Bartesaghi; Osmond, Paul; Peters, Alan; Irger, Matthias
Abstract: This paper presents a methodological framework for a more accurate assessment of the thermal performance of green infrastructure (GI) using a combination of airborne remote sensing, field measurements and numerical modelling. The proposed framework consists of: (a) controlling intervening variables and classifying sites according to urban morphology, (b) classifying GI according to a newly developed typology, (c) quantifying and allocating a set of indicators/metrics to each typology, and (d) analysing and comparing data spatially and statistically. The proposed framework provides a standardised protocol that urban planners and practitioners can apply to quantify, compare and report the results of microclimate studies.